Equipping future nurses: readiness of nursing students in addressing intimate partner violence in China - Chen, Le; Mohd Zain, Norhasmah; Bakar, Raishan Shafini; Qin, Qin; Xu, Ershan; Tang, Shu; Chen, Hongtao; Huang, Zhixing; Chen, Jing (Frontiers in Public Health, 2025)
AimThis study aimed to evaluate the readiness of nursing students in China to respond to patients experiencing intimate partner violence (IPV) and to identify key influencing factors.BackgroundNurses play a crucial role in providing care and support to IPV survivors. However, limited research has examined the extent to which nursing students are prepared for this responsibility. Gaining insights into their level of readiness and the factors that shape it is essential for informing educational strategies and policy development.DesignA cross-sectional study was conducted among 532 nursing students recruited from four public universities in Hunan Province, China, via multistage sampling.MethodsData were collected using validated instruments, including the Readiness to Encounter Partner Abuse Patients (READI) Scale and the Modified Physician Readiness to Manage Intimate Partner Violence Survey (PREMIS). Pearson correlation analyses were conducted to examine the associations among perceived knowledge, attitudes, skill preparedness, and readiness. Logistic regression (LR) was employed to identify significant predictors of readiness, and mediation analyses were performed to assess the intermediary roles of perceived knowledge, skill preparedness, and attitudes.Results82.7% of participants reported poor readiness to respond to IPV cases. Significant predictors of readiness included perceived knowledge (OR=2.938; 95% CI: 2.246–3.931), skill preparedness (OR=3.592; 95% CI: 2.700–4.095), attitudes (OR=4.472; 95% CI: 1.925-10.800), IPV-related education (OR=2.654; 95% CI: 1.297–5.230), and IPV training experience (OR=3.072; 95% CI: 1.444–6.310). Mediation analyses further revealed that both perceived knowledge and skill preparedness partially mediated the relationship between IPV training and readiness.ConclusionThe study identified a substantial gap in the readiness of nursing students to manage IPV-related cases, underscoring the critical need to enhance educational and training programs. Incorporating comprehensive IPV-related content into nursing curricula may significantly improve preparedness and foster survivor-centered care within the healthcare system.